Investigation of Food Supply Chain Sustainability Performance for Turkey's Food Sector - Yontar, Emel; Ersöz, Süleyman (Frontiers in Sustainable Food Systems, 2020)
Increasing product demands, environmental aspects and overpopulation have an impact on the sustainability of a supply chain, especially in the food sector. In a food supply chain from production to consumption, there are many parameters (resources, packaging, waste management etc.) that need to be taken into account for sustainability. The aim of this study is to determine the parameters affecting sustainable food supply chain management for the food sector and to measure the performance of the parameters along the supply chain. In this study, several performance indices are defined and sub-criteria by reviewing the previously discussed indices in the literature and accounting for expert opinions on the sustainable food supply chain. The parameters are explained as customer satisfaction, resource utilization, safety of products, innovation, reliability, company information, packaging, waste management dimensions that should be improved in sustainable food supply chain management. Performance score for each dimension is calculated with Structural Equation Modeling and Analytic Hierarchy Process. As a result of the sustainable food supply chain performance evaluation made in the food sector in Turkey it is determined to be 79,7 out of 100. The results of this study include feedbacks on parameters in the food chain from agriculture to consumers.